Penerapan Media Interaktif Berbasis Gemini Canvas Melalui Interactive Flat Panel dalam Pembelajaran Membaca Cerita Rakyat Berbasis Kearifan Lokal Pada Siswa Kelas V SD Negeri 01 Dukuh - Kusmartini, Yuliasih; Widayati, Mukti; Sudiyana, Benedictus (GERAM (Gerakan Aktif Menulis), 2026)
This study aims to describe the implementation of Gemini Canvas-based interactive media through an Interactive Flat Panel in teaching folklore reading based on local wisdom to elementary school students and its impact. A descriptive qualitative approach with a naturalistic design was employed. Data included reading activities, student interactions, engagement, evaluation results, and responses from both the teacher and students. Data were collected through observations of the learning process, aloud reading, group discussions, and interactive media usage; interviews with the fifth-grade teacher and students; and documentation of teaching modules, materials, worksheets, assessment instruments, and activity photos. Data sources consisted of the fifth-grade teacher, 15 fifth-grade students, and the reading instruction process at SD Negeri 01 Dukuh. Data validity was ensured using source and method triangulation. The interactive data analysis model involved data reduction, data display, and conclusion drawing. The results showed that reading instruction progressed through planning, implementation, and evaluation stages integrated with Gemini Canvas-based interactive media featuring local wisdom folklore. Reading comprehension evaluations revealed that 10 out of 15 students (66.7%) achieved good and excellent categories. Furthermore, learning activities demonstrated high student engagement through confident aloud reading, active group discussions, and participation in interactive sessions.